2019
DOI: 10.1093/ajh/hpz005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gestational Diabetes Is Associated With Offspring’s Hypertension

Abstract: Gestational diabetes mellitus (GDM) accounts for approximately 7% of all pregnancies in the United States and China. 1,2 Women with GDM are at an increased risk of adverse pregnancy outcomes, such as giving birth to babies with greater birth weight and primary cesarean delivery. 3 Maternal GDM also exerts a long-term influence on the offspring, which was named "metabolic imprinting" by some researchers. 4 Previous studies indicated that offspring of mothers with GDM were predisposed to metabolic syndrome and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 33 publications
(30 reference statements)
3
52
1
Order By: Relevance
“…Then FPG, FINS and HOMA-IR levels of three groups of patients were compared. The results were consistent with another research ( 20 ), and IR level in GDM group significantly increased. Therefore, it was confirmed that insulin resistance was one of the physiological and pathological bases of GDM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Then FPG, FINS and HOMA-IR levels of three groups of patients were compared. The results were consistent with another research ( 20 ), and IR level in GDM group significantly increased. Therefore, it was confirmed that insulin resistance was one of the physiological and pathological bases of GDM.…”
Section: Discussionsupporting
confidence: 93%
“…However, the pregnancy process was a physiological insulin resistance state, but not all pregnant women had gestational diabetes, and some returned to normal after delivery ( 19 ). In order to further illustrate that insulin resistance is one of the pathophysiological bases of GDM, GDM had more severe IR than normal pregnancy ( 20 ). Clinically, the main indexes for diagnosis of insulin resistance were FPG level and FINS level.…”
Section: Discussionmentioning
confidence: 99%
“…Only those predicted targets involved in ontologies of human diseases (obesity, hypertension, glucose intolerance, lipid metabolism disease, type 2 diabetes mellitus, heart septal defects and heart valve disease, heart disease, heart failure, venous insufficiency, and pulmonary embolism) reported by previous population-based cohort studies in children and young adults descending from GDM complicated pregnancies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] are presented below.…”
Section: Methodsmentioning
confidence: 99%
“…Young offspring aged 3–5 years of GDM complicated pregnancies were reported to have increased BMI, skinfold thickness, body fat, blood pressure, altered lipid profiles, and glucose metabolism [ 26 ]. Several consecutive studies confirmed higher mean values of systolic blood pressure and higher prevalence of hypertension in young offspring (at the age of 3–6 years) of mothers with GDM compared with their counterparts born to mothers with a normal course of gestation [ 27 , 28 ]. An independent association between the occurrence of maternal GDM and abnormal glucose tolerance, obesity, and higher BP was confirmed in children at seven years of age [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the postpartum can return to normal, but the chance of developing type 2 diabetes is greatly increased. The poor blood sugar control during pregnancy is also prone to polyhydramnios [47] and pregnancy-induced hypertension [48,49]. The main pregnancy complications include late preterm birth [50], hyperlipidemia [51], and posttraumatic stress disorder and antepartum complications [52].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%